Assessing residential front yards using Google Street View and geospatial video: A virtual survey approach for urban pollinator conservation. (March 2018) - Burr, Andrea; Schaeg, Nicole; Hall, Damon M.
Abstract: Google Street View and geospatial video mapping have been successfully employed to inventory neighborhood environments in a variety of disciplines. However, virtual survey approaches have yet to be leveraged fully for fine-scale auditing of ecological characteristics in urban contexts. Here we propose a method combining Google Street View and geospatial video mapping to virtually inventory vegetation composition over time in residential front yards to assess habitat for native pollinator conservation. As a proof of concept, it bolsters the feasibility and effectiveness of virtual approaches to conduct fine-scale street-level audits of neighborhood environments. Additionally, the findings inform future science-based education and outreach interventions at two study sites. Highlights: Urban residential yards can play an important role in native bee conservation. We use virtual surveying approaches to conduct fine-scale audits of front yards. These audits create longitudinal data for assessing yards for bee habitat composition. Our proof-of-concept case combines two virtual survey methods for fine-scale audits. Results inform science-based community education and outreach interventions.